2009
DOI: 10.1021/pr801065s
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Human Dentin Reveals Distinct Protein Expression Profiles

Abstract: The human tooth is the hardest organ of the body, and is composed of enamel, dentin, and dental pulp. Dentin provides the basis of the tooth shape by lining the inner parts of the root and crown. Odontoblasts deposit dentin, an organic matrix that contains collagen, noncollagenous proteins, phospholipids, and growth factors. In this study, we sought to reveal the proteins in human dentin by using liquid chromatography-tandem mass spectroscopy (LC-MS/MS) proteomic approaches. Human third molar dentins were cut,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 50 publications
8
95
5
1
Order By: Relevance
“…The organic matrix of dentin is known to contain 233 total and 68 common proteins, including a variety of collagenous and noncollagenous proteins such as DSP, biglycan, osteoglycin, OPN, and OCN; as well as various matrix and serum proteins deposited in the dentin, including asporin, lumican, mimecan and SOD3 [43]. This study found that TDM expressed COL-I, DMP1, BSP, DSP, OPN, TGF-b 1 , decorin and biglycan.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The organic matrix of dentin is known to contain 233 total and 68 common proteins, including a variety of collagenous and noncollagenous proteins such as DSP, biglycan, osteoglycin, OPN, and OCN; as well as various matrix and serum proteins deposited in the dentin, including asporin, lumican, mimecan and SOD3 [43]. This study found that TDM expressed COL-I, DMP1, BSP, DSP, OPN, TGF-b 1 , decorin and biglycan.…”
Section: Discussionmentioning
confidence: 72%
“…This study found that TDM expressed COL-I, DMP1, BSP, DSP, OPN, TGF-b 1 , decorin and biglycan. Under the effect of these factors, the stronger multi-differentiating DFCs differentiated into functional odontoblasts [43], which is key for dentin regeneration. Most importantly, this study showed that induced DFCs strongly expressed COL-I and secreted a rich matrix, which is also one of the typical features of odontoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoskeletal keratins were also identified, but they are an expected contamination in MS analysis. 19 Brown and yellow enamel lanes showed more abundant serum albumin and alpha-1-antitrypsin as evidenced by band intensity and the frequencies of database matches. For example, the peptides identified from the mass spectrometry data (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, after the determination that co-purifying bone morphogenic proteins 2 and 3 are the source of its growth stimulatory activity, the protein was renamed osteoglycin (Dash et al 1993). A novel finding of the previous study showed that Mimecan (osteoglycin) was detected at high levels in dentin, what is more, the immunoreactivity of Mimecan in human dentin was more intense than that in human mandibular bone (Park et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…What is more, mRNA levels of Mepe, Dspp were increased in a time-dependent manner in human dental pulp cells undergoing odontoblastic differentiation (Wei et al 2009). Additionally, the proteins identified in human dentin using liquid chromatography-tandem mass spectroscopy (LC-MS/MS) proteomic approaches included Dspp and Mimecan (Park et al 2009). All the date indicate the correlation among those mineralization related proteins in tooth germ development.…”
Section: Introductionmentioning
confidence: 99%